Moving Past "Progressive" Prosecution in the Wake of the Trump Administration - Maybell Romero (Washington University Journal of Law and Policy, 2022)
The Trump presidency seemed to relish conflict and reliably used it as a political tool, fomenting it further by engaging in “racist rhetoric . . . and socially divisive policies.” This tool was exemplified in Trump’s messaging on criminal law and policy, which was often confusing and contradictory. Given President Trump’s “Law and Order” messaging and his flagrant and theatrical support of the police, it is not surprising to look back and see that a major rise of the “progressive prosecution” movement aligns very closely in time to the Trump years. This Essay looks at the interrelationship between the Trump administration and progressive prosecutors throughout the country, illuminating how self-described progressive prosecutors postured in opposition to Trump. It then examines how the progressive prosecutor movement reacted to losing one of its main antagonists. The author argues that the term “progressive prosecutor” has, in essence, become vacant, meaningless, and political, and that rather than perpetuating the use of such a label, another should be instituted in its place that emphasizes forward-looking problem solving as advocated in the American Bar Association’s Standards for the Prosecution Function.
Keywords: Trump; President; Donald; Presidency; Political; Racism; Rhetoric; Divisive; Policy; Prosecutor; Criminal; Law; Progressive; Prosecution; Administration; ABA; American; Bar; Association; Justice; Police